IMPLEMENTASI MODEL PROJECT BASED LEARNING MENGGUNAKAN MEDIA YOUTUBE PADA KEMAMPUAN MENULIS TEKS EKSPOSISI SISWA FASE F DI SMA NEGERI 10 KOTA JAMBI - fenicitranola, Feni Citra Nola; Sophia Rahmawati; Siti Enik Mukhoiyaroh Bambang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The article entitled "Implementation of Project Based Learning Model Using YouTube Media on Students' Exposition Text Writing Ability Phase F at SMA Negeri 10 Jambi City" aims to describe the implementation of Project Based Learning (PjBL) model assisted by YouTube media and its impact on students' exposition text writing ability. This study is limited to grade XI students Phase F at SMA Negeri 10 Jambi City and focuses on the learning process and the results of students' writing abilities after the implementation of the learning model. The study uses a qualitative approach with a case study type. Data collection is carried out through observation, interviews, and documentation, while data analysis uses an interactive analysis model that includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that in the initial stage students' understanding of exposition text is still low, especially in identifying text structures and developing arguments. After the implementation of the Project Based Learning model using YouTube media, students are able to analyze elements of exposition text such as main ideas, facts or data, causes, and impacts better. The results of the writing assessment showed that most students obtained good to very good categories with an average class score of around 85. This finding indicates that the implementation of Project Based Learning assisted by YouTube media can create more active, contextual, and effective learning in improving students' expository text writing skills.